Maternal and partner's level of satisfaction on the delivery room service in University of Gondar Referral Hospital, northwest, Ethiopia: a comparative cross-sectional study - Asefa Adimasu Taddese; Kiros Terefe Gashaye; Henok Dagne; Zewudu Andualem (BMC, 2020)
Abstract Background Asking patients/clients what they perceive about the care and treatment they have received is one of the important steps towards improving the quality of health care. In the scientific world, a number of efforts have been tried to understand about what laboring mothers perceive about the care provided. However, little is known about the birth experiences of partners in Ethiopia. Therefore, this study was aimed to assess the maternal and partner's level of satisfaction on the delivery room service in the study area. Methods A comparative cross-sectional study was conducted from December 2018 to January 2019 in University of Gondar referral hospital. The birth satisfaction scale is used for the mother, and it was adapted to the partners' perspective. Paired-samples t tests were used for comparing mothers and partners for the birth satisfaction scales global and thematic scores. A binary logistic regression model was fitted to identify predicting factors for mothers' and partners satisfaction. Results The overall satisfaction of mothers in this study was 47.6%. Whereas, 41.2% of partners were satisfied by delivery room services. There were mean difference between mothers and partners' birth satisfaction scale (p = 0.02). Maternal satisfaction scale was affected by age [OR = 0.36, 95%CI (0.18, 0.73)], perception [OR = 0.02, 95%CI (0.001,0.09)], waiting time [OR = 0.11, 95%CI (0.001, 0.09)],visiting mode [OR = 0.01, 95%CI (0.001,0.08)], pregnancy status [OR = 0.04, 95%CI (0.01,0.33)] and fatal outcome [OR = 0.001, 95%CI (0.001,0.018)] .whereas, partners satisfaction was associated with age [OR = 0.16,95%CI (0.05 0.49)], occupational status [OR = 0.02, 95%CI (0.001, 0.24), amount of money to pay for service [OR = 2.87, 95%CI (1.07, 7.71), visiting mode of his wife [OR = 0.08, 95%CI (0.01, 0.35)], waiting time [OR = 0.12, 95%CI (0.04, 0.33)], privacy [OR = 10.61, 95%CI (3.00, 37.52)], mode of delivery of his wife [OR = 7.69, 95%CI (3.00, 19.69)]. Conclusion This finding would alert the health care system to design a client-friendly approach. It will provide insight to hospital administrators and providers in formulating a policy that would enhance the support of partners during labour and delivery process.